Clinical versus pathological staging in laryngectomized patients - Cristina Aguiar; Mónica Teixeira; Paulo Pina; Edite Coimbra Ferreira; Leandro Ribeiro; Pedro Oliveira (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Aim: To assess the accuracy of clinical staging in laryngeal and hypopharyngeal cancer, as well as its impact on the type of treatment and associated factors